The dilemma faced by the people of Poso District, Sausu District, Central Sulawesi against the East Indonesia Mujahideen (MIT) group and the role of the National Police in Overcoming it - Aulia, Reva; Meliala, Adrianus Eliasta; Salya, Sundawan (International Journal of Social Service and Research, 2023)
The conflict that occurred in Poso Regency, Central Sulawesi, Sausu District has been going on for a long time and has not been resolved.  The East Indonesia Mujahideen (MIT) groups carried out shooting actions against security forces and carried out Amaliyah attacks on community settlements that had claimed many victims. The community begins to dilemma on the one hand, if they provide information to the Police then their safety is also threatened, and vice versa if the community does not provide information to the Police then the community can be categorized as MIT sympathizers. The sympathizers are organized into 4 quadrants consisting of active sympathizer groups, passive groups, agent groups and apathetic groups. The purpose of this study is to see changes in community behavior before and after Madago Raya security operations towards social dilemmas that occur in the people of Poso Regency. This research uses qualitative methods where the data obtained through interviews and documentation studies. Interviews were conducted with informants who had been designated, secondary data that had been obtained and then analyzed using triangulation data analysis techniques to obtain research results.